O ensino de filosofia africana e a (des)construção de práticas metodológicas - MACEDO, Raelma dos Santos Nascimento (2023)
From the restlessness of the silence of philosophical reflections from other cultures, mainly from the African continent, in the teaching of philosophy. The present work weaves together a set of discourses about the absence of epistemic diversity, the centrality of European thought, and the exclusion and disqualification of non-Western philosophies, especially African and Afro-diasporic philosophy in the teaching of philosophy in high school. The work aims to insert the teaching of African and Afro diasporic philosophy in accordance with the philosophy of tradition in a plural way, without impositions of universalities, through a didactic sequence that offers alternatives for a plural teaching practice, decentralizing the Eurocentric axis of the teaching of philosophy, in a dialogue with the productions of African, Afro-descendant and Aphrodisasporic philosophers, initially the work highlights the category of race and racism strengthened in the colonial process, the inferiorization of Africans and their culture and the racialization of reason. A dialogue between Heidegger and Towa about the identity of philosophy. In the following moment, Eurocentrism and epistemicide are discussed, the approval of law 10.639\03 and the mandatory teaching of African and Afro-descendant history and culture and the teaching of philosophy, the absence of African and Afrodiasporic philosophy in the textbook and finally presents a Participatory research carried out at the Graça Aranha school in Imperatriz-Ma, developed with third-year high school students, presented as a didactic support proposal for teachers, as an example of a way to teach philosophy that breaks with racist ideals of exclusivism epistemological .